The Effects of the Modifiers in English on Thai Learners - Kongkaew, Prommin (มนุษยสังคมสาร (มสส.) คณะมนุษยศาสตร์และสังคมศาสตร์ มหาวิทยาลัยราชภัฏบุรีรัมย์, 2022)
This article aims to describe the modifiers in English and show how they can have an effect on Thai learners’ learning of English. The modifiers are the important elements of the grammatical structure of English. They can affect learners’ learning development in a number of ways. Understanding the modifiers in English can be beneficial to Thai learners. Generally, the modifiers in English are classified into a pre-modifier and a post-modifier. Comparatively speaking, the fist can have more effect on Thai learners because it is different from the modifiers in Thai language. Hence Thai learners of English are more likely to make more errors. The second is less likely to cause learners to make mistakes as the word orders in English and Thai are more or less similar. Hence, Thai learners are less prone to errors. However, errors in the post-modifier may occur if the head word has longer post-modifiers.